The Implementation of Nahdlatul Ulama's Moderation Philosophy in Treating Islamic Fundamentalism in Bandar Lampung - Maulana Mukhlis; Ahmad Robi Ulzikri; Angger Widianto (IAIN Ponorogo, 2021)
The Islamic fundamentalism movement has metamorphosed into a serious threat to the existence of multiculturalism in Bandar Lampung. This movement turned into a social and educational movement that penetrated educational institutions in Lampung. It transformed into a campus organization. Not only the state, Islamic religious-based civil society organizations with moderate views such as Nahdlatul Ulama often intersect directly with Islamic fundamentalism groups. The Islamic purification brought by this group has often become a space for friction with Nahdlatul Ulama (Henceforth: NU). Moreover, there are study forums on-campus that discuss Islamic law and the caliphate (Khilafah) system as the Unitary system of the Republic of Indonesia. This has become a point of controversy with NU groups that accept Pancasila as the final foundation of the state. This study aims to find out how Nahdlatul Ulama Bandar Lampung City through its basic philosophy faces the contradiction of the Islamic fundamentalism movement and what challenges are faced by NU with the Islamic fundamentalism group in Bandar Lampung. The research method used is descriptive qualitative in which data are obtained through interview techniques. The results showed the contradiction of NU Bandar Lampung against Islamic fundamentalism groups holding on to the basic philosophy, namely tawassuth and i'tidal, tasamuh, and tawazun. Besides, community activities based on strengthening moderatism of Ahlussunah wal Jamaah annahdliyyah, and the attitude of tolerance among religious communities are based on the attitude of serving the people (fii khidmatil ummah). Future challenges for NU Bandar Lampung include internal challenges (increasing the quality of resources and the identity of the NU) and external challenges (environment and global change). الملخص: تحولت حركة الأصولية الإسلامية إلى تهديد خطير لوجود حياة التعددية الثقافية في بندر لامبونخ. هذه الحركة تصبح الحركات الاجتماعية والتعليم التي تتخلل المؤسسات التعليمية في لامبونخ. صارت هذه الحركات الي منظمة الجامعة. ليس فقط الدولة، منظمة المجتمع الإسلامي مع أيديولوجية معتدلة مثل نهضة العلماء كثيرا ما تتقاطع في تعارض مباشر مع مجموعة الأصولية الإسلامية في وسط المجتمع. غاليا يصبح تطهير الإسلام الذي نقل بهذه المجموعة غرفة المُنَاوَشَة بمنظمة نهضة العلماء. لاسيما بوجود منتدى الأبحاث الذي ينوي في تكوين الشريعة الإسلامية والخلافة كنظام للدولة الموحدة لجمهورية إندونيسيا. لقد أصبح هذا الفرق التعارض بنهضة العلماء التي تقبل المبدئ الخمسة كدولة نهائية. تهدف هذه الدراسة إلى تحديد كيفية مواجهة نهضة العلماء في بندرلامبونج من خلال فلسفة الجوهر في أداء تناقض مع حركة الأصولية الإسلامية وكذلك التحديات التي تواجهها نهضة العلماء في مواجهة مجموعة الأصولية الإسلامية في بندر لامبونج. طريقة البحث المستخدمة في هذا البحث هي نوعية وصفية، والبيانات التي تم الحصول عليها من خلال تقنيات المقابلة. أظهرت هذه نتائج البحث أنّ تناقضات نهضة العلماء في بندر لامبونج على مجموعة الأصولية الإسلامية التمسك الفلسفة هي التوسط والاعتدال، والتسامح، والتوازن، من خلال أنشطة المجتمع التي تعزز الاعتدال على أساس اهل السنة والجماعة النهضية، والتسامح بين الأديان على أساس خذمة الأمة. التحديات التي تنتظرها نهضة العلماء في بندرلامبونج تشمل على التحديات الداخلية (موارد تحسين الجودة وهوية نهضة العلماء) والتحديات الخارجية (التغيرات البيئية والعالمية). اAbstrak: Gerakan fundamentalisme Islam telah bermetamorfosa menjadi sebuah ancamam serius terhadap eksistensi kehidupan multikulturalisme di Bandar Lampung. Gerakan ini bermetamoforsis menjadi gerakan gerakan sosial dan pendidikan yang merasuk ke dalam lembaga-lembaga pendidikan di Lampung. Ia menjelma menjadi organisasi kampus dan bahkan mengkooptasinya. Tidak hanya negara, organisasi masyarakat sipil berbasis agama Islam dengan faham moderat seperti Nahdlatul Ulama kerap bersinggungan langsung dalam kontradiksi terhadap kelompok fundamentalisme Islam di tengah masyarakat. Purifikasi Islam yang dibawa kelompok ini sering menjadi ruang gesekan dengan NU. Terlabih adanya forum-forum kajian di kampus yang mewacanakan syariat Islam dan khilafah sebaga sistem negara Kesatuan Republik Indonesia. Hal ini menjadi titik gegesakan dengan kalangan NU yang menerima Pancasila sebagai Dasar negara yang sudah final. Penelitian ini bertujuan untuk mengetahui bagaimana vis a vis Nahdlatul Ulama Kota Bandar Lampung melalui falsafah dasarnya dalam melakukan kontradiksi terhadap gerakan fundamentalisme Islam serta tantangan yang apa saja yang dihadapi NU dalam vis a vis dengan kelompok fundamentalisme Islam di Bandar Lampung. Metode penelitian yang digunakan adalah deskriptif kualitatif, data diperoleh melalui teknik wawancara. Hasil penelitian menunjukan kontradiksi NU Bandar Lampung terhadap kelompok fundamentalisme Islam berpegangan pada falsafah dasar yaitu tawassuth dan i’tidal, sikap tasamuh, dan sikap tawazun, melalui kegiatan-kegiatan masyarakat yang bersifat penguatan sikap moderatisme berdasarkan Ahlussunah wal Jamaah annahdliyyah, sikap toleransi antar umat beragama berlandaskan pada sikap mengabdi kepada umat (fii khidmatil ummah). Tantangan kedepan bagi NU Bandar Lampung meliputi tantangan internal (peningkatan kualitas sumberdaya dan identitas ke-Nu-an) dan tantangan eksternal (lingkungan dan perubahan global).